2021
DOI: 10.3389/fnhum.2021.732946
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Analysis in Motor-Imagery Brain Computer Interfaces

Abstract: Motor Imagery BCI systems have a high rate of users that are not capable of modulating their brain activity accurately enough to communicate with the system. Several studies have identified psychological, cognitive, and neurophysiological measures that might explain this MI-BCI inefficiency. Traditional research had focused on mu suppression in the sensorimotor area in order to classify imagery, but this does not reflect the true dynamics that underlie motor imagery. Functional connectivity reflects the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 86 publications
2
18
0
Order By: Relevance
“…The dataset used in this study consisted of bipolar derivations, instead of unipolar channel values that are more commonly used in the qEEG analysis [24,29]. The use of bipolar derivations is seen as a more advantageous method compared to unipolar or average referencing methods [33], as it can mitigate the issues associated with common active referencing such as volume conduction [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset used in this study consisted of bipolar derivations, instead of unipolar channel values that are more commonly used in the qEEG analysis [24,29]. The use of bipolar derivations is seen as a more advantageous method compared to unipolar or average referencing methods [33], as it can mitigate the issues associated with common active referencing such as volume conduction [34].…”
Section: Discussionmentioning
confidence: 99%
“…For every subject, the PLV was calculated for all possible 253 bipolar channel combinations in five frequency bands as defined above. Next, inspired by [29],…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…One possible reason for these results is that the decrease in functional connectivity may be related to the cognitive load required for MI. Indeed, Leeuwis et al found that functional connectivity during the resting state was greater than that during MI in both BCI illiterate and BCI literate subjects (Leeuwis et al, 2021). Mylonas et al have shown that the decrements of phase synchronization at the alpha and beta bands are associated with the sensorimotor integration that contributes to motor performance (Mylonas et al, 2016).…”
Section: Variation In Functional Connectivitymentioning
confidence: 99%
“…In addition, we assumed that poor BCI performers may have greater potential to change their brain activity through learning or external stimulation, for either better or worse, compared to high BCI performers because high BCI performers' brain activity may be stable and optimal already. To divide the subjects into low and high BCI performance groups, a previous study used the median value of the BCI performance [29], as the median value can divide groups with the same size and allow analysis to be performed on sub-groups of the same size. However, the distribution and sample size affect the median value.…”
Section: Bci Performance Evaluationmentioning
confidence: 99%
“…They found that the subjects bene ted from brain network features (functional connectivity), and suggested that low performers may engage in motor imagery differently than high performers, and thus existing features, such as ERD, cannot capture the engagement although the brain network showed the possibility. Similarly, another study divided the subjects recruited into two groups based upon BCI performance, compared their brain networks on multiple network scales [29], and found signi cantly higher phase synchronization values in the right hemisphere during high performers' motor imagery. In addition to brain network measures, a difference between low and high BCI performers' frequency band power has been reported during the rest or pre-stimulus period, showing that subjects with higher alpha band or sensory motor rhythm (SMR) power during those periods are more likely to achieve better BCI performance [30][31][32].…”
Section: Introductionmentioning
confidence: 99%